Smoking Habit and Coffee Consumption with Gastritis Incidence Rate at Productive Ages - Wibowo, Elsi Septira; Margo, Eveline (Global Medical & Health Communication (GMHC), 2024)
Gastritis is a disease caused by an inflammation of the mucous and submucosal lining of the stomach. Several studies show that there is an influence of smoking habit and coffee consumption on gastritis incidence rate. The study was to determine the correlation between smoking habit and coffee consumption toward gastritis at productive ages. The research is an analytical observational study with a cross-sectional design conducted in Makale Health Center, South Sulawesi, in February 2020. Required data was gathered by conducting guided interviews using a questionnaire that includes age range, sex, and education level. Brinkman Index was used to measure smoking habits, coffee consumption, and gastritis questionnaire. Data was analyzed using a chi-square test with a significance level of p=0.05. From a total of 115 respondents, there are 69.6% included in the age range of 26–35 years old, 58.3% have mild smoking habits, 56.5% have severe coffee consumption, and 85.2% are suffering from gastritis. There is a relation between smoking habit (p=0.029) and coffee consumption (p=0.003) with gastritis (p<0.05). The conclusion is that there is a relationship between smoking habits, coffee consumption, and gastritis incidence.